Trends in primary school teachers’ experience over the first year of the COVID-19 pandemic in Serbia: A narrative analysis - Mićić, Katarina; Kovács Cerović, Tünde; Vračar, Selena (Psihološka istraživanja, 2021)
The purpose of the study is to explore the experiences shared by primary school teachers in three waves of data collection. Teachers’ narratives about their experiences of schooling during the COVID-19 pandemic were elicited online. In three instances, a total of 116 participants were prompted to narrate in story and letter genres, providing 233 narratives. We conducted the values analysis and additionally analysed data statistically in order to compare the values teachers expressed at three key turning points for education in the first year of the COVID-19 pandemic in Serbia. Altogether, three major values and nine value codes were identified. This multi-genre three-wave approach provided a nuanced and comprehensive picture of teachers’ most important impressions, concerns, and strategies in the new reality, in particular as the emphasis changed over the course of one year of the pandemic. Teachers who took part in the first wave mostly focused on health and prevention issues, their duties, the workload, and the strategies for coping with the new normal. In the second wave, as the threat eased, teachers expressed increased awareness of schooling related issues. Teachers’ narratives in the third wave primarily focused on the learning process and outcomes. Based on the conducted analyses, the paper draws policy recommendations.